Road to Paris 2024: force-velocity profile in different speed climbers’ abilities - de la Cruz, Violeta Muñoz; Carranza, Víctor Rodrigo; González Ravé, José María (Biology of Sport, 2024)
Speed climbing will be a new discipline in Paris 2024. The physical requirements of speed climbing are different from the other climbing modalities due to the short event time requiring higher level of strength and power. These parameters have been measured through the Force Velocity (F-V) profile in different climbing disciplines. However, there are no known results evaluating different speed climbing abilities to establish whether F-V relationship is a determining factor between performance levels. The purpose of this study was to evaluate the upper and lower limbs F-V profile in different speed climbing abilities considering sex. Twenty six speed climbers were divided into two groups based on their level of performance: international level (men n = 7 and women n = 2) and national level (men n = 8 and women n = 7). Participants performed pull-ups and squat incremental tests and F-V profile variables [Maximum theorical values of force (F 0 ), velocity (V 0 ) and power (P max )], one-repetition maximum value (1RM) and %1RM where peak power was expressed were collected using a linear encoder. There were significant differences in F 0 , relative force, %1RM where peak power was expressed, and 1RM in pull-ups ( p < 0.05) between groups. However, there were not significant differences between groups in squat variables. No significant sex differences were found in any variable. There were moderate-strong correlations between running time and 1RM (pull-ups and squat), F 0 and FV-slope (pull-ups) ( p < 0.05) analyzed in the whole group. In conclusion, F 0 and 1RM in pull-ups were significantly higher in international climbers. Therefore, national climbers should focus their training on improving force by training with heavy loads. Additionally, squat F-V profile variables do not seem to be as important as in the pull-up for performance.